Early combined parenteral and enteral nutrition for pancreaticoduodenectomy – Retrospective cohort analysis. (March 2016) - Probst, Pascal; Keller, Daniel; Steimer, Johannes; Gmür, Emanuel; Haller, Alois; Imoberdorf, Reinhard; Rühlin, Maya; Gelpke, Hans; Breitenstein, Stefan
Abstract: Background: Suggested guidelines for nutritional support after pancreaticoduodenectomy are still controversial. Recent evidence suggests that combining enteral nutrition (EN) with parenteral nutrition (PN) improves outcome. For ten years, patients have been treated with Early Combined Parenteral and Enteral Nutrition (ECPEN) after PD. The aim of this study was to report on rationale, safety, effectiveness and outcome associated with this method. Methods: Consecutive PD performed between 2003 and 2012 were analyzed retrospectively. Early EN and PN was standardized and started immediately after surgery. EN was increased to 40 ml/h (1 kcal/ml) over 24 h, while PN was supplemented based on a daily energy target of 25 kcal/kg. Standard enteral and parenteral products were used. Results: Sixty-nine patients were nutritionally supplemented according to ECPEN. The median coverage of kcal per patients related to the total caloric requirements during the entire hospitalization (nutrition balance) was 93.4% (range: 100%–69.3%). The nutritional balance in patients with needle catheter jejunostomy (NCJ) was significantly higher than in the group with nasojejunal tube (97.1% vs. 91.6%; p < 0.0001). Mortality rate was 5.8%, while major complications (Clavien-Dindo 3–5) occurred in 21.7% of patients. Neither the presence of preoperative malnutrition nor the application of preoperative immunonutrition was associated with postoperative clinical outcome. Conclusion: This is the first European study of ECPEN after PD. ECPEN is safe and, especially in combination with NCJ, provides comprehensive coverage of caloric requirements during the postoperative phase. Clinical controlled trials are needed to investigate potential benefits of complete energy supplementation during the early postoperative phase after PD. Highlights: ECPEN is one possible nutritional technique after pancreaticoduodenectomy. The coverage of caloric requirements per patient was 93.4%. The coverage was higher in patients with needle catheter jejunostomy. With ECPEN malnutrition or immunonutrition did not affect outcomes.